Návrh na zlepšení spokojenosti zákazníků kavárny Akademie Caffé - Michalová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Diplomová práce se zabývá marketingovým výzkumem spokojenosti zákazníků kavárny Akademie Caffé a následným vyhodnocením tohoto výzkumu na základě dotazníkového řešení. Důležitou součástí práce jsou také návrhy a doporučení, které vedou ke zvýšení spokojenosti zákazníků, a tím i ke zvýšení tržeb a získání lepšího postavení na trhu.

This master´s thesis deals with marketing research of customer satisfaction of Akademie Caffé and subsequent evaluation of this research based on questionnaire as a research instrument. An important part of this work are also suggestions and recommendations that lead to increased satisfaction, thereby increasing sales and gaining a better position in the market.
The Proposal of Customer Satisfaction Improvement of Akademie Caffé
Keywords: Marketingový výzkum; spokojenost zákazníků; dotazník; respondenti; analýza; návrhy; propagace; reklama; zlepšení kvality.; Marketing research; customer satisfaction; questionnaire; respondents; analysis; proposals; promotion; advertising; quality improvement.